2019
DOI: 10.3390/met9010109
|View full text |Cite
|
Sign up to set email alerts
|

Forming Process, Microstructure, and Mechanical Properties of Thin-Walled 316L Stainless Steel Using Speed-Cold-Welding Additive Manufacturing

Abstract: Wire and arc additive manufacturing (WAAM) produces thin-walled parts superior to other additive manufacturing methods, because of its high efficiency, good compactability, and low cost. However, the WAAM accuracy is limited by its large heat input. Here, 0.8 mm 316L stainless steel welding wire is deposited via speed cold welding to form 30-layered thin-walled samples, with 2 mm thickness, and up to 65 mm height. The effects of three process parameters (the bottom current mode, scanning speed, and cooling tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…A thin and tall sample, G3010 (gradual reduction of bottom current, scanning speed was 30 cm/min, cooling time was 10 s), had uniform layer height, as demonstrated in Figure 3a. Through the samples in Figure 3b, Wu et al [96] found that gradual reduction of current improves bottom formation. welding additive manufacturing.…”
Section: Macroscopic Characteristics Of Samplesmentioning
confidence: 97%
See 3 more Smart Citations
“…A thin and tall sample, G3010 (gradual reduction of bottom current, scanning speed was 30 cm/min, cooling time was 10 s), had uniform layer height, as demonstrated in Figure 3a. Through the samples in Figure 3b, Wu et al [96] found that gradual reduction of current improves bottom formation. welding additive manufacturing.…”
Section: Macroscopic Characteristics Of Samplesmentioning
confidence: 97%
“…A thin and tall sample, #GRBC-30 cm/min-10 s G3010 (gradual reduction of bottom current, scanning speed was 30 cm/min, cooling time was 10 s), had uniform layer height, as demonstrated in Figure 3a. Through the samples in Figure 3b, Wu et al [96] found that gradual reduction of current improves bottom formation. As shown in Figure 3a,c (samples G3010and G3510), the increase in scanning speed leads to a decrease in the deposition rate, resulting in the unevenness on the outer surface.…”
Section: Macroscopic Characteristics Of Samplesmentioning
confidence: 97%
See 2 more Smart Citations
“…In Figure 6, the red crossings represent poor morphology, and the red solid circles indicate good morphology but higher heat input for the low speed. Under the same arc mode, the grain size would be coarse and the performance would be degraded for large heat input [22], so these points were all not the optimal process parameters. From the above analysis, it could be seen that no matter how the speed changed by CMT+P process, as the WFS was 2.5 m/min, the deposition was not continuous and the right part cocked, while when WFS reached to 5.5 m/min, the molten metal began to flow.…”
Section: #Cp5mentioning
confidence: 99%